The Rise of Scientific Research in Corporate America - Arora, Ashish; Belenzon, Sharon; Kosenko, Konstantin; Suh, Jungkyu; Yafeh, Yishay (Organization Science, 2025)
It is widely believed that university and corporate research are complementary: companies invest in research in part to develop the capacity to absorb the knowledge emerging from universities. However, as we show in this paper, corporate research in the United States emerged when American universities were behind the world frontier in scientific research. Why, then, did for-profit businesses choose to invest in creating new knowledge, much of which could spill over to rivals, and whose conduct presented many managerial challenges? We argue that corporate research in America arose in the 1920s to compensate for weak university research, not to complement it. Using newly assembled firm-level data from the 1920s and 1930s, we find that companies invested in research because inventions increasingly relied on science but American universities were unable to meet their needs. Large firms close to the technological frontier and operating in concentrated industries were likely to invest in research, especially in scientific disciplines where American universities lagged behind the scientific frontier. Corporate science seems to have paid off, resulting in novel patents and high market valuations for firms engaged in research. Funding: A. Arora, S. Belenzon, and J. Suh acknowledge support from the Fuqua School of Business, Duke University. S. Belenzon and Y. Yafeh gratefully acknowledge financial support from the Israel Science Foundation [Grant No. 963-2020]. K. Kosenko is grateful for support from the Bank of Israel. Y. Yafeh acknowledges support from the Krueger Center at the Hebrew University of Jerusalem School of Business. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.18053 .